Considerações sobre o projeto, cálculo e detalhamento de vigas pré-fabricadas protendidas com aderência inicial em pavimentos de edificações - Inforsato, Thiago Bindilatti (2009)
This work shows a calculation sequence to determine and detail the longitudinal and transverse reinforcement of prestesses beams with pre-composed section. All procedures are done in a way that meets all the requirements of NBR6118: 2003 and 9062:2006 Code. It shows how the checks can be made of the ultimate state limit and the cracking service state and determining whether there is need for the isolation of the strand. The prestesses loss are considered taking into account the age of the constituents of the concrete section at the time when each step is performed and the procedure for progressive loss. The assumptions adopted for the calculation as composite section and the respective transverse reinforcement are detailing. It can be done as the detailing of transverse reinforcement with special care for the end of the piece where it is common the use of dapped-end. Four numerical examples are solved showing how the recommended calculation sequence allows the designer immediately realize the best solution, including the need for the use of prestressed strand along the top edge. The results obtained in the examples it can be seen: the advantage of using the section Ibeam, the semi-rigid connection has a limited efficiency even with large amounts of negative reinforcement, because the existence of the dapped-end, that considering the effect of prestressing causes the shear reinforcement required is minimal. Finally we can conclude that in several instances the situation critical for obtaining the longitudinal reinforcement was in service with the decompression.